Design, synthesis, antimicrobial evaluation and molecular docking studies of some new 2, 3-dihydrothiazoles and 4-thiazolidinones containing sulfisoxazole. (3rd March 2016) - Nasr, Tamer; Bondock, Samir; Eid, Sameh
Abstract: Microbial resistance to the available drugs poses a serious threat in modern medicine. We report the design, synthesis and in vitro antimicrobial evaluation of new functionalized 2, 3-dihydrothiazoles and 4-thiazolidinones tagged with sulfisoxazole moiety. Compound8d was most active against Bacillis subtilis (MIC, 0.007 µg/mL). Moreover, compounds7c –d and8c displayed significant activities against B. subtilis and Streptococcus pneumoniae (MIC, 0.03–0.06 µg/mL and 0.06–0.12 µg/mL versus ampicillin 0.24 µg/mL and 0.12 µg/mL; respectively). Compounds7a and7c –d were highly potent against Escherichia coli (MIC, 0.49–0.98 µg/mL versus gentamycin 1.95 µg/mL). On the other hand, compounds7e and9c were fourfolds more active than amphotericin B against Syncephalastrum racemosum . Molecular docking studies showed that the synthesized compounds could act as inhibitors for the dihydropteroate synthase enzyme (DHPS). This study is a platform for the future design of more potent antimicrobial agents.